Comparative antioxidant, antiproliferative and apoptotic effects of Ilex laurina and Ilex paraguariensis on colon cancer cells (2014)
ABSTRACT: To determine and compare the antioxidant, antiproliferative and apoptotic effects of leaf infusions of Ilex laurina and Ilex paraguariensis in colon cancer cells. Methods: Antioxidant activity was determined by ORAC (Oxygen Radical Absorbance Capacity) and FRAP (Ferric Reducing Antioxidant Power). Cytotoxic and antiproliferative effects were analyzed using MTT ((3-(4, 5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide) and sulfhorodamine-B respectively. Cell death and apoptosis of human colon adenocarcinoma cells SW480 and their metastatic-derived SW620 cells, were analyzed by flow cytometry using propidium iodide and Annexin-V. Results: Although their flavonoid levels were similar, I. laurina infusion contained 2.2 and 4.4 times higher amounts of total phenolic and caffeoyl derivatives, respectively, than I. paraguariensis. FRAP and ORAC values for I. laurina infusion were 1.6 and 2.0 more active than I. paraguariensis. Both plant infusions inhibited viability and cell growth of SW480 and SW620 cells. These results may be associated to cell cycle-arrest and apoptosis because of the comparable increase of hypodiploid and annexin-V positive colon cancer cells. Conclusion: These data highlight the antioxidant and promising anticancer activities of I. laurina and Ilex paraguariensis.